Thermal Conductivity in Concrete Samples with Natural and Synthetic Fibers - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
One crucial property of concrete, particularly in construction, is its thermal conductivity, which impacts heat transfer through conduction. For example, reducing the thermal conductivity of concrete can lead to energy savings in buildings. Various techniques exist for measuring the thermal conductivity of materials, but there is limited discussion in the literature about suitable methods for concrete. In this study, the transient line source method is employed to evaluate the thermal conductivity of concrete samples with natural and synthetic fibers after 7 and 28 days of curing. The results indicate that concrete with hemp fiber generally exhibits higher thermal conductivity values, increasing by 48% after 28 days of curing, while synthetic fibers have a minimal effect. In conclusion, this research opens the door to using natural alternatives like hemp fiber to improve concrete’s thermal properties, providing alternatives for thermo-active foundations and geothermal energy piles which require high thermal conductivities. © 2024 by the authors.